Synopsis of current developments: Computer application in sports - Baca, A. (The Engineering of Sport 6, Volume 3 Developments for Innovation, 2006)
Research activities are strongly affected by actual developments in computer science, such as in the areas of hardware (increasing processor speed and storage capacity, advances in communication technology), software (powerful tools), information management (data bases, data mining) and media (internet, eLearning, multimedia).